2017
DOI: 10.1007/s00383-017-4170-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two-staged Fowler–Stephens laparoscopic orchidopexy (FSLO) for intra-abdominal testes (IAT)

Abstract: The success rate of FSLO was 68.6%. None of the above-described independent variables have any effect on the outcome of two-staged FSLO. While VILO remains the treatment of choice for IAT located at or near the ring, but IAT higher than this, two-staged FSLO gives a better chance for achieving intra-scrotal orchidopexy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…NPT accounts for 20–35% of UDT, and NPT patients often have short spermatic cord, which have been a challenge for surgeons ( 15 17 ). After the exclusion of non-viable testes, NPT can be classified into intra-abdominal and intracanalicular testes according to the location of the testis ( 4 , 15 ). Various surgical strategies are currently available to address this problem.…”
Section: Discussionmentioning
confidence: 99%
“…NPT accounts for 20–35% of UDT, and NPT patients often have short spermatic cord, which have been a challenge for surgeons ( 15 17 ). After the exclusion of non-viable testes, NPT can be classified into intra-abdominal and intracanalicular testes according to the location of the testis ( 4 , 15 ). Various surgical strategies are currently available to address this problem.…”
Section: Discussionmentioning
confidence: 99%
“…15 Bagga et al reported a success rate of 68, 6% in the application of two-stage FS orchidopexy and they affirmed that two stages gave a better opportunity to achieve intrascrotal orchidopexy. 16 If we consider the complications of FSLO, the rate of atrophy reported in the large series varied from 4% to 17%. Alagaratnam et al found an incidence of testicular atrophy of 8.8% in 94 patients operated on with FS orchidopexy.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative outcome reporting is variable, but includes testicular atrophy, ascent, and volume discrepancy compared to the contralateral testis. Successful outcomes (a testis in the scrotum) have been reported at 66.7-92% [14][15][16][17][18][19] for FSLO, with a systematic review indicating an overall 85% success rate [20]. However, some authors have reported significantly smaller post-operative testicular volumes compared with the contralateral, normally descended testis [17].…”
Section: Discussionmentioning
confidence: 99%